Numerical simulation of the Tayler instability in liquid metals - Norbert Weber; Vladimir Galindo; Frank Stefani; Tom Weier; Thomas Wondrak (New Journal of Physics, 2013)
The electrical current through an incompressible, viscous and resistive liquid conductor produces an azimuthal magnetic field that becomes unstable when the corresponding Hartmann number exceeds a critical value of the order of 20. This Tayler instability (TI), which is not only discussed as a key ingredient of a nonlinear stellar dynamo model (Tayler–Spruit dynamo), but also as a limiting factor for the maximum size of large liquid metal batteries, was recently observed experimentally in a column of a liquid metal (Seilmayer et al 2012 Phys. Rev. Lett. 108 244501). On the basis of an integro-differential equation approach, we have developed a fully three-dimensional numerical code, and have utilized it for the simulation of the Tayler instability at typical viscosities and resistivities of liquid metals. The resulting growth rates are in good agreement with the experimental data. We illustrate the capabilities of the code for the detailed simulation of liquid metal battery problems in realistic geometries.